Digital Travel Experience Influencing Passenger Loyalty in Full-Service Airlines - Tharekes, Lalitlak (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2026)
This research aimed to: (1) examine the digital travel experiences of full-service airline passengers; (2) investigate passenger loyalty to full-service airlines; and (3) analyze the influence of digital travel experiences on passenger loyalty. The study employed quantitative research design using questionnaires. The population consisted of Thai passengers aged 20 years and older who had traveled with full-service airlines. The sample size was determined using Cochran’s formula with a 95% confidence level and a 5% margin of error, resulting in a total of 385 respondents selected through convenience sampling. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics through simple linear regression analysis. The results indicated that: (1) respondents reported very good digital experiences before and during travel, and moderate experiences after travel; (2) passengers demonstrated very high levels of both attitudinal and behavioral loyalty toward full-service airlines; and (3) overall digital experiences across all stages of travel—before, during, and after—were at a moderate level. The study further revealed that pre-travel digital experiences significantly influenced passenger loyalty to full-service airlines at the 0.01 level of statistical significance. Notably, pre-travel digital experiences had the strongest impact on both behavioral and attitudinal loyalty. These findings suggest that airlines can enhance passenger satisfaction and strengthen loyalty by improving their digital technology systems and developing integrated platforms that include check-in, baggage tracking, flight delay notifications, gate information, and mileage accumulation within a single application.